Da submissão à feminização masculina: subversões de gênero no BDSM - Silva, Marcelle Jacinto da (2013)
We propose to discuss the subject of gender performance within the context ofthe practices of erotic sadomasochism or BDSM, that elaborate discursively their experiences in blogs and identify as submissive and / or practitioners ofmale feminization.